Seismic reliability evaluation of steel gabled frames consisting of web-tapered members using joint analysis of hazard and fragility. (March 2022) - Malekizadeh, Mohammad; Fanaie, Nader; Pirasteh, Ali Akbar
Abstract: Despite the wide application of steel gabled frame (SGF) systems in large industrial projects, the current literature lacks accurate information on their seismic performance to ensure satisfactory performance at different levels of earthquake intensity. Also, given the scant information on the structural performance and their seismic design parameters in most of the available guidelines, the use of joint analysis of hazard and fragility can be very important, since both the reference hazard on site and the structural performance are considered. To address this issue, in the present paper, incremental dynamic analysis (IDA) was performed using 20 ground motions on four SGFs and their results were collected in the form of fragility curves. Then to obtain the annual rate of exceedance, hazard curves of the study region were generated and combined with the fragility curves, and finally, the seismic reliability of SGFs was evaluated at design basis earthquake (DBE) and maximum considered earthquake (MCE) hazard levels. Seismic reliability results indicated that the available seismic design guidelines lead to a too conservative design for SGFs, especially when they have long periods, where at the MCE hazard level, long-period SGFs with about 58% safety margin do not even experience LS performance level. The results of this study can prove useful for a more efficient design of SGFs in seismic regions.